2008
DOI: 10.1016/j.physletb.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of antihyperons in nuclei with antiprotons

Abstract: A simple method to explore the interaction of antihyperons in nuclei by exclusive hyperon-antihyperon pair production close to threshold in antiproton nucleus interactions is proposed. Due to energy and momentum conservation event-by-event transverse momentum correlations of the produced hyperons and antihyperons contain information on the difference between their potentials. A schematic Monte Carlo simulation is used to illustrate the sensitivities of the proposed method for the reaction 1.66GeV/c antiproton+… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…short distances [15]. Taking G-parity transformation [16] as a guidance a direct comparison of the interactions of baryons with that of antibaryons in nuclei may help to shed light on the nature of short-range baryon-baryon forces [17].…”
Section: Tackling Cold Superdense Hadronic Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…short distances [15]. Taking G-parity transformation [16] as a guidance a direct comparison of the interactions of baryons with that of antibaryons in nuclei may help to shed light on the nature of short-range baryon-baryon forces [17].…”
Section: Tackling Cold Superdense Hadronic Mattermentioning
confidence: 99%
“…Antihyperons annihilate quickly in normal nuclei and spectroscopic information is therefore not directly accessible. In future quantitative information on the antihyperon potentials may be obtained via exclusive antihyperon-hyperon pair production close to threshold in antiproton-nucleus interactions [15]. Once these hyperons leave the nucleus and are detected, their asymptotic momentum distributions will reflect the depth of the respective potentials.…”
Section: Tackling Cold Superdense Hadronic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative information on the antihyperon potentials relative to that of the corresponding hyperon may be obtained via exclusive antihyperon-hyperon pair production close to threshold in antiproton-nucleus interactions [21]. Once these hyperons leave the nucleus and are detected, their asymptotic momentum distributions will reflect the depth of the respective potentials.…”
Section: Introductionmentioning
confidence: 99%
“…However, since in the pp center-of-mass the distribution of the produced baryon-antibaryon pair will usually not be isotropic, the analysis can rely only on the transverse momenta of the outgoing baryons. In [21] it was demonstrated that the individual transverse momentum distributions alone do not allow to extract unambiguous information on the potential of antihyperons. Instead the transverse momentum asymmetry α T defined in terms of the transverse momenta of the coincident particles can be used to explore eventby-event correlations:…”
Section: Introductionmentioning
confidence: 99%